Salinity induced physiological responses in juvenile dusky kob, Argyrosomus japonicus (Sciaenidae) - Bernatzeder, Andrea Katinka (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2009)
Fisheries management regulations for dusky kob Argyrosomus japonicus, an important commercial and recreational fisheries species, have failed and the stock is considered collapsed. It is important to take an ecosystems approach to management which includes understanding the effect of environmental factors on recruitment, abundance and distribution. The distribution of early juveniles (20-150 mm TL) in the wild appears to be restricted to the upper reaches of estuaries at salinities below 5 psu. Food availability could not explain the distribution of early juveniles. The aim of this study was to investigate the role of salinity on the distribution of early juvenile dusky kob (<150 mm TL) by examining physiological responses of juveniles exposed to a range of salinities under laboratory conditions. The hypothesis was that the physiological functioning of early juveniles would be optimised at the reduced salinities which they naturally occur at. The objectives of this study were to investigate the effect of salinity on: i) plasma osmolality; ii) growth, food conversion ratio and condition factor; and iii) gill histology with emphasis on chloride cell size and number. A preliminary study was undertaken to determine whether the use of 2-phenoxyethanol had an effect on plasma osmolality. Juveniles pithed prior to blood sampling were used as the control. Plasma osmolality was not affected by exposure or duration of exposure (2, 4, 6, 8, 10 min) to 2-phenoxyethanol. The ability of teleosts to regulate plasma osmolality over a wide range of salinities indicates their degree of 'physiological euryhalinity'. Plasma osmolality of juveniles exposed to 5, 12 and 35 psu was measured every two weeks over a total of six weeks. Although juveniles were able to regulate plasma osmolality over the duration of the experiment, plasma osmolality at 5 and 12 psu was significantly lower than in fish maintained at 35 psu. Growth is used as an indicator of the relative energy used for osmoregulation at different salinities, as the energy used for osmoregulation becomes unavailable for growth. A nineweek growth experiment was conducted on juveniles exposed to 5, 12 and 35 psu. Juveniles grew and survived at all three salinities. However, growth of juveniles at 5 psu was significantly lower than at 12 and 35 psu. Other than a significantly greater weight gain at 35 psu relative to 12 psu, there was no significant difference in specific growth and length gain between juveniles at 12 and 35 psu. Food conversion ratio and condition factor at 12 and 35 psu were not significantly different, but food conversion ratio and condition factor at 5 psu was significantly greater and lower than at 35 psu respectively. In fish, gills are considered the major organ involved in osmoregulation. Within the gills, chloride cells are the predominant site of ion exchange which is driven by the Naâ º, Kâ º- ATPase enzyme. Gill samples of juveniles exposed to 5, 12 and 35 psu for six weeks were examined histologically using light microscopy. Chloride cells of juveniles maintained at 5 psu were significantly more abundant than in juveniles at 12 and 35 psu. Chloride cells of juveniles at 5 psu were significantly larger than in juveniles kept at 12 psu, but not significantly different to those of juveniles kept at 35 psu. The ability of the juvenile fish to regulate plasma osmolality indicates that they are 'physiologically euryhaline', but the reduced growth and proliferation of chloride cells at 5 psu suggests that energy expenditure for osmoregulation is increased at hypoosmotic salinities. Salinity induced physiological responses could therefore not explain the natural distribution of early juvenile dusky kob and it is proposed that other environmental factors (e.g. temperature) are also important. It is also hypothesised that the high conductivity of an estuary in South Africa, to which our understanding is limited, may negate the effect of reduced salinity. Although freshwater input into estuaries is an important factor, further investigations to explain the distribution and abundance of early juveniles is required to make management recommendations. Dusky kob is also becoming an increasingly popular aquaculture species in South Africa. In this regard, early juvenile dusky kob can be grown at salinities as low as 12 psu without negatively affecting growth and production.
Keywords: Osmoregulation; Argyrosomus -- Effects of salt on -- South Africa; Sciaenidae -- Effects of salt on -- South Africa; Argyrosomus -- Physiology; Sciaenidae -- Physiology; Fishes -- Physiology; Biological control systems; Marine ecology -- South Africa; Fishery management -- South Africa; Mariculture -- South Africa